Penyuluhan tentang Infeksi Menular Seksual pada Wanita Pekerja Seks di Lokalisasi Km. 12 Palangka Raya - Suryagustina Suryagustina; Eva Priskila; Cyntia Christin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Sexually transmitted infections (STIs) are one of the causes of health, social and economic problems in many countries. According to WHO STIs are infections that are transmitted through vaginal, anal and oral sexual intercourse. Based on the results of a preliminary survey in the area many FSWs (Female Sex Workers) did not know about STIs. This counseling aims to increase the knowledge of FSWs to be able to prevent the transmission of STIs both for themselves and for the community in Prostitution Area. 12th-kilometer Palangka Raya City. The method used in this service is in the form of lectures, discussions, question and answer and evaluation with a pre-post-test, with a sample of 25 respondents. The results of this service show that there is an increase in WPS knowledge about STIs as evidenced by pre-test data 32% lacking knowledge, 64% sufficient knowledge and only 4% good knowledge, after being given information post-test 56% good knowledge, 44% sufficient knowledge there is no lack of knowledge. The conclusion from the results of the service shows the influence of health education on the level of knowledge of respondents. It is hoped that the results of this service can be an effort to prevent the spread of STIs for FSWs and the community